Protein Assistants of Small Ribosomal Subunit Biogenesis in Bacteria - Elena Maksimova; Olesya Kravchenko; Alexey Korepanov; Elena Stolboushkina (Microorganisms, 2022)
Ribosome biogenesis is a fundamental and multistage process. The basic steps of ribosome assembly are the transcription, processing, folding, and modification of rRNA; the translation, folding, and modification of r-proteins; and consecutive binding of ribosomal proteins to rRNAs. Ribosome maturation is facilitated by biogenesis factors that include a broad spectrum of proteins: GTPases, RNA helicases, endonucleases, modification enzymes, molecular chaperones, etc. The ribosome assembly factors assist proper rRNA folding and protein–RNA interactions and may sense the checkpoints during the assembly to ensure correct order of this process. Inactivation of these factors is accompanied by severe growth phenotypes and accumulation of immature ribosomal subunits containing unprocessed rRNA, which reduces overall translation efficiency and causes translational errors. In this review, we focus on the structural and biochemical analysis of the 30S ribosomal subunit assembly factors RbfA, YjeQ (RsgA), Era, KsgA (RsmA), RimJ, RimM, RimP, and Hfq, which take part in the decoding-center folding.